DEVELOPMENT AND MASTERING OF PRODUCTION TECHNOLOGY OF GRINDING BODIES IN DISPOSABLE SAND- CLAY MOLDS - I. A. Busel; I. E. Omelchenko; L. Z. Pisarenko; V. M. Priemko (Литьë и металлургия, 2011)
The carried out experimental and scientific-research works enabled to organize mass production of grinding bodies, which being successfully tested at the enterprises of building industry of the Republic of Belarus now.